Analysis of intraoral microvascular anastomosis in maxillofacial defects reconstruction. Issue 1 (January 2023) - Zhang, Hong-Yu; Shao, Zhe; Jia, Jun; Liu, Bing; Bu, Lin-Lin
Abstract: This review summarizes the research progress in the field of intraoral microvascular anastomosis techniques (IAT) and attempts to investigate the indications for procedures in which IAT can be applied, the surgical procedure and the difficulties involved, technical assessments, result evaluation and the perspective. Currently, microvascular anastomosis technique is widely used in maxillofacial defects reconstruction from various causes including cutaneous injury or congenital deformity which usually required extensive flap reconstruction and therefore a vascular free flap is routinely used. Conventional microvascular anastomosis reconstruction techniques cannot avoid new incisions, which will affect the postoperative aesthetic situation. Surgeons have therefore attempted to improve this technique to effectively eliminate scars caused by surgery: some patients can be chosen to undergo microvascular anastomosis of the free flap intraorally, thus reducing the extraoral incision caused by the anastomosis located in neck or maxillofacial improving the postoperative appearance of the patients. In addition to preserving the external appearance, intraoral anastomosis technique (IAT) can also solve some other problems of maxillofacial vascular anastomosis, such as insufficient vessel pedicle length and high risk of facial nerve injury.